2000
DOI: 10.1002/1099-1654(200007/08)10:4<231::aid-rmv290>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and impact of resistance against approved antiretroviral drugs

Abstract: More than 15 antiretroviral drugs are now available for clinical use, and have led to signi®cant reductions in morbidity and mortality for HIV infected individuals. Nevertheless, antiviral drug resistance emerges to all these drugs, which limits their bene®t. This review addresses the biological basis of antiretroviral drug resistance, and the prevalence of speci®c drug resistance associated mutations in patients treated with the three currently available classes of agents, namely nucleoside analogue reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 23 publications
0
45
0
Order By: Relevance
“…(NRTIs), non-nucleoside reverse-transcriptase inhibitors (NNRTIs) and protease inhibitors (PIs) (Pillay et al, 2000). Resistance-associated mutations in the viral reverse-transcriptase (RT) and protease (P) genes are classed as primary if their presence alone confers resistance to a particular drug.…”
Section: Introduction and Definitionsmentioning
confidence: 99%
“…(NRTIs), non-nucleoside reverse-transcriptase inhibitors (NNRTIs) and protease inhibitors (PIs) (Pillay et al, 2000). Resistance-associated mutations in the viral reverse-transcriptase (RT) and protease (P) genes are classed as primary if their presence alone confers resistance to a particular drug.…”
Section: Introduction and Definitionsmentioning
confidence: 99%
“…On the other hand, some mutations were correlated to possible resistance against reverse transcriptase inhibitors in two never treated patients with long-lasting infection. In the absence of drug selection, the wild type virus did not re-emerge as expected though several published reports suggested that, in the absence of drug selection, mutations initially present might revert over time to wild type because of its better replicative capacity [4,14,18,[26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several codon substitutions not correlated to key mutations and probably occurring as spontaneous genetic polymorphisms [18,30,31], were detected in several patients belonging to both groups. The overall frequency of secondary mutations in the protease gene was significantly greater than that observed in reverse transcriptase, probably due to the polymorphic nature of the protease gene that may lead to a heterogeneous response to protease inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations